The Success of Teachers in Implementing the Curriculum in Statistics Subjects - Ramatni, Ali (Journal of Education Reseach and Evaluation, 2025)
Negative mindset and attitude towards statistics lessons have an impact on interest in learning. Facts show that the teaching methods of statistics materials used by teachers in Indonesia are less than optimal. The gap between the theory of expectations and reality in the field is urgent to research to analyze the attitudes of prospective teachers towards statistics and differences in attitudes between genders. The research method used is quantitative with a Survey approach. The sample was 641 teachers spread across Sungai Penuh. Data collection techniques with Surveys with instruments. This scale uses a Likert scale from 1 strongly disagree to 7 strongly agree. The analysis technique used is descriptive statistics with the help of SPSS Version 25.0 to calculate the mean, standard deviation, and T-test. Alpha factor analysis and confirmatory Cronbach are used to test reliability and validity. The attitudes of prospective teachers and analyzed using SPSS version 25.0 and CFA was analyzed using SPSS AMOS 25.0. The results found that teachers' attitudes were in the good and positive categories towards the four components of the model. It was also found that female teachers had more positive attitudes towards statistics than male teachers. The study concludes that teachers in statistics learning are encouraged to learn independently with the preparation and training received, and teachers' attitudes and skills are increasingly developing with frequent training. The implications of this study are for the development of teacher learning processes in the classroom by attending training more often and using exercises and discussions in statistics learning.